Finite element analysis modeling research on the compression process of cotton fiber assembly. Issue 11 (June 2020) - Xu, Minjun; Chen, Xiaochuan; Wang, Jun; Li, Yong
In order to analyze the compressive stress state of a cotton fiber assembly in the compression process, a new cotton fiber assembly model, the tetrakaidecahedral porous cotton fiber assembly model, is presented based on the idea of three-dimensional open-cell foam material modeling. Based on the model, the compression process of cotton fiber assembly is analyzed using the finite element method. The change in the compressive stress of the cotton fiber assembly in the compression process is successfully described. The measurement method of compressive modulus of the cotton fiber assembly is also studied, and the relation between compressive modulus and relative density of the cotton fiber assembly is determined. Finally, the effect of different moisture regain on compressive stress of the cotton fiber assembly is analyzed, and the reference value of moisture regain in the cotton baling process is given. The results show that the simulation results are consistent with the actual situation. Therefore, the established model of cotton fiber assembly has validity.